CEO characteristics, ownership, and earnings management in Indonesian public listed companies with two-tier boards / Doni Sagitarian Warganegara, Norhayati Mohamed and Imbarine Bujang - Warganegara, Doni Sagitarian; Mohamed, Norhayati; Bujang, Imbarine (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2024)
The issue of how board characteristics and ownership concentration affect managerial behavior remains unresolved, especially in a two-tier governance system. This study investigated the impact of ownership concentration, CEO age, and gender on real earnings management (REM) in Indonesia. It determined how these factors affect managerial opportunism within REM, an underexplored area in Indonesian corporate governance. This study employed the Roychowdhury model and data from 191 Indonesian listed companies (2015-2019), analysing 955 observations with static panel analysis via OLS, random, and fixed effects. The findings indicated a positive, significant, but moderate association between ownership concentration and abnormal production costs, an indicator of REM activity. Additionally, the negative relationship between CEO age and abnormal discretionary expenses suggests that older CEOs are less likely to employ aggressive REM strategies. This study demonstrated that ownership concentration, CEO age, and CEO gender did not significantly impact grey earnings management in a two-tier board system. These results highlight the need for governance reforms to improve transparency, accountability, and ethical standards in Indonesia's financial reporting. They highlight aligning management practices with shareholder interests to reduce managerial opportunistic behaviour.